Is Daytime Systolic Load an Important Risk Factor for Target Organ Damage in Pediatric Hypertension?. Issue 10 (3rd July 2015) - Conkar, Seçil; Yılmaz, Ebru; Hacıkara, Şükriye; Bozabalı, Sibel; Mir, Sevgi
<x xml:space="preserve">Abstract</x> The aim of this study was to compare ambulatory blood pressure (BP) monitoring (ABPM) data and determine which hypertension type is a risk factor in target organ damage. A total of 82 children (47 boys) with suspected hypertension based on office BP measurements and considered hypertensive by ABPM were studied. Target organ damage included the following: 35.3% hypertensive retinopathy, 25.6% microalbuminuria, 15.8% increased left ventricular mass index, 29.2% increased carotid intima‐media thickness (cIMT), 24.3% high augmentation index (AIx), and 19.5% high pulse wave velocity (PWV). The association between BP load, PWV, and cIMT was statistically significant. There were significant correlations between daytime systolic BP load, PWV, AIx, and cIMT. A statistically significant difference was also detected between nighttime systolic BP load, PWV, and cIMT values and nighttime diastolic BP load levels and values of AIx and cIMT. There was also a statistically significant difference between the high level of nighttime diastolic BP load and cIMT. The authors found that target organ damage was seen more often in children with primary hypertension who had systolic loads.